Penerapan model problem-based learning untuk meningkatkan hasil belajar matematika peserta didik - Saputro, Agus; Murni, Atma; Saragih, Sehatta (Jurnal Pendidik Indonesia, 2025)
This study aims to enhance the quality of the learning process and improve students' mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model. PBL is an instructional approach that encourages active student engagement in solving contextual problems to build a deeper conceptual understanding. The method used is classroom action research (CAR), with data collected through observation sheets of teacher and student activities, as well as mathematics learning outcome tests. The research subjects were students of class VIII-2 at MTs YPI Kuala Enok, Indragiri Hilir Regency. The results showed that before the implementation, only 20% of students achieved the Minimum Mastery Criteria (MMC). After the first cycle, this percentage increased to 56.66%, and in the second cycle, it rose to 86.66%. This improvement was also accompanied by enhancements in the learning process in each meeting. Thus, the implementation of the PBL model proved to be effective in improving the learning process and enhancing students’ mathematics learning outcomes.